International experience of formation and implementation of anticorruption policies in other states - Rostovska, Kateryna (Actual problems of law (Aktual’ni problemi pravoznavstva), 2018)
The article analyzes the international law and the experience of other states in the formation and implementation of anti-corruption policy in foreign countries. The urgent issues of implementation of foreign experience in the field of counteraction to corruption are considered